Bilateral Serous Detachment Associated with Latanoprost/Timolol Fixed Combination Use: A Report of One Phakic Case - Esra Ayhan Tuzcu; Ugurcan Keskin; Mesut Coskun; Ozgur Ilhan; Mutlu Daglıoglu; Huseyin Oksuz (Case Reports in Ophthalmological Medicine)
We present a case of bilateral diffuse serous detachment associated with latanoprost/timolol fixed combination treatment which was recovered after changing treatment.